The World almanac and book of facts (Press Pub. Co, 2007)
Since its debut in 1868, The World Almanac and Book of Facts has become the bestselling American reference book of all time, with more than 80 million copies in print. This essential household and workplace desk reference is "the most useful reference book known to modern man," according to the L.A. Times. Renowned New York Times crossword puzzle editor Will Shortz calls it his "#1 reference work for facts." Plus, this year, for the first time ever, The World Almanac offers readers free bonus content online at www.worldalmanac.com, through a password provided with the book. World Almanac buyers can peruse classic World Almanac essays, facts and figures from past presidential elections, sports biographies, and cover art from The World Almanac's 139-year history. Below you'll find exclusive examples of some of the bonus content you'll find online.